2012
DOI: 10.1002/ijc.27597
|View full text |Cite
|
Sign up to set email alerts
|

Modest increase in risk of specific types of cancer types in type 2 diabetes mellitus patients

Abstract: Most studies associated diabetes mellitus (DM) with risk of cancer have focused on the Caucasian population and only a few types of cancer. Therefore, a large and comprehensive nationwide retrospective cohort study involving an Asian population was conducted to evaluate the risk of several major types of cancer among Type 2 DM patients. The study analyzed the nationwide population-based database from 1996 to 2009 released by the National Health Research Institute in Taiwan. Incidence and hazard ratios (HRs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
65
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 33 publications
13
65
0
2
Order By: Relevance
“…As biological evidence, a dose-response meta-analysis revealed that every 0.56 mmol/L increase in fasting blood glucose was associated with a 14% increase in the rate of pancreatic cancer13. Although the association between T2DM and lung cancer has been suggested, the conclusions were inconsistent in studies1415161718. Overall, our findings supported the hypothesis that the risk of developing lung cancer increase in T2DM patients, particularly among women.…”
Section: Discussionsupporting
confidence: 72%
“…As biological evidence, a dose-response meta-analysis revealed that every 0.56 mmol/L increase in fasting blood glucose was associated with a 14% increase in the rate of pancreatic cancer13. Although the association between T2DM and lung cancer has been suggested, the conclusions were inconsistent in studies1415161718. Overall, our findings supported the hypothesis that the risk of developing lung cancer increase in T2DM patients, particularly among women.…”
Section: Discussionsupporting
confidence: 72%
“…Because of differences in apparent relationships between diabetes and the various types of malignancy, analyses of associations with all-cause cancers have been discouraged (8). However, the consistency of the results of this and other studies (22,23,24,26,27) suggests that there is a moderate diabetes-specific increase in overall cancer risk. Possible unifying underlying mechanisms include direct promotion of cell growth and an increase in the likelihood of metastasis through altered endothelial permeability by hyperglycaemia (28), while hyperinsulinaemia and elevated circulating insulin-like growth factor concentrations may also promote tumour growth (29).…”
Section: Discussionmentioning
confidence: 78%
“…Ten case-control studies 3,19-27 and 14 cohort studies 4,10,11,[28][29][30][31][32][33][34][35][36][37][38] were included in the meta-analysis. Analysis of all studies showed that, compared with individuals without DM, those with DM had a statistically significant increased risk of bladder cancer (RR 1.30, 95% CI 1.18-1.43) (Fig.…”
Section: Dm and Bladder Cancer Riskmentioning
confidence: 99%